Dispersal network heterogeneity affects ecosystem stability in rock-paper-scissors tournaments - Guo, Guanming; Zhang, Helin (Frontiers in Ecology and Evolution, 2025)
IntroductionIt is a critical issue in ecology to identify mechanisms of biodiversity maintenance. Many theoretical studies have revealed that intransitive competition among species on shared dispersal networks can promote species coexistence,while little attention is paid to the effect of unshared dispersal networks on ecosystem stability. The classic intransitive competition in an ecological community is the rock-paper-scissors game,where species A excludes B, B outcompetes C, and C can displace A.MethodsHere, we explore the relationships between dispersal network heterogeneity and rock-paper-scissors dynamics by using a cellular automation model with its underlying species abundances and extinction generation.ResultsOnly one species remains in the ecosystem eventually when all species utilize the same dispersal network and the extinction of generations of the first species is the lowest on a scale-free network under the same condition. On the contrary, the fluctuation size of ecological dynamics is negatively correlated with dispersal network heterogeneity on unshared networks. Ecosystem stability is a paradox, namely, between shared and unshared networks. Furthermore, the dispersal rates of species also show the opposite result for ecosystem stability on shared vs. unshared networks.DiscussionTherefore, we represent a potential maintenance mechanism of biodiversity.